Free Radical Scavenging Activity of Gliclazide in Type 2 Diabetic Mellitus Patients (Tikrit Journal of Pharmaceutical Sciences, 2023)
To evaluate the effects of 8 weeks of gliclazide therapy on serum glucose level and serum malondialdehyde (MDA) as a marker of lipid peroxidation in newly diagnosed type 2 diabetes mellitus (T2DM) patients. Thirty newly diagnosed T2DM patients were participated in the study (15 males and 15 females) with mean age of (47.55+-8.46) years .A thirty healthy subjects (15 male and 15 females ) of matching age were also recruited in the study as control group. Both groups were matched regarding age, sex and BMI. Fasting serum glucose (FSG) concentration was estimated using a kit supplied by Biocon (Germany). Serum MDA was measured using thiobarbituric acid (TBA) chemical assay method. Showed that T2DM patients having a significant rise in marker of lipid peroxidation MDA and FSG before starting treatment as compared with the control group. After 8 weeks of gliclazide monotherapy there was a significant reduction in both FSG and MDA level. Gliclazide having free radical scavenger properties showed from the decrease in lipid peroxidation in addition to its hypoglycemic effects